1966
DOI: 10.1530/jrf.0.0110303
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Purified Sheep Luteinizing Hormone on the Guinea-Pig Ovary

Abstract: Luteinizing hormone (Ovine, from the National Institutes of Health, Bethesda, U.S.A.) has been administered subcutaneously in normal saline (0\m=.\5mg/ml) to female guinea-pigs for a study of The induced and cyclic corpora lutea were examined in three females killed 7 days after the lh injection given on luteal Day 7; the two types were histologically distinguishable. In one female both sets of corpora lutea had regressed and the follicles were pre-ovulatory. In another, both sets still looked large and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1966
1966
1985
1985

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…It has also been suggested that oestrogen may be inducing luteal regression in pregnant guinea-pigs by affecting pituitary gonadotrophic secretions (Deanesly, 1963). It is unlikely that the luteolysis induced by oestrogen in our study involved a stimulation or inhibition of lh secretion, since this hormone has neither luteotrophic nor luteolytic effect in the cyclic guinea-pig (Deanesly, 1966). Oestrogen exerts a luteolytic and an anti-folliculotrophic effect in the hamster.…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…It has also been suggested that oestrogen may be inducing luteal regression in pregnant guinea-pigs by affecting pituitary gonadotrophic secretions (Deanesly, 1963). It is unlikely that the luteolysis induced by oestrogen in our study involved a stimulation or inhibition of lh secretion, since this hormone has neither luteotrophic nor luteolytic effect in the cyclic guinea-pig (Deanesly, 1966). Oestrogen exerts a luteolytic and an anti-folliculotrophic effect in the hamster.…”
Section: Methodsmentioning
confidence: 49%
“…Oestrogen exerts a luteolytic and an anti-folliculotrophic effect in the hamster. These effects can be reversed by suitable doses of pmsg, hcg or fsh, but not lh (Greenwald, 1965 (Aldred et al, 1961;Rowlands, 1962;Deanesly, 1966) were unsuccessful. However, fsh was not used in these studies.…”
Section: Methodsmentioning
confidence: 99%
“…Up to 56 days after hysterectomy, the original corpora lutea were still of maximum normal size in five out of seven hysterectomized guinea-pigs, in which treatment with lh had induced fresh corpora lutea 7 to 18 days earlier (Deanesly, 1966). In the other two females, 36 and 52 days after hysterectomy, the original corpora lutea were not up to full size, but this probably represented normal variation rather than the effects of induced ovulations.…”
Section: Corpora Lutea Of Hysterectomy After Induced Ovulationmentioning
confidence: 86%
“…In preliminary experiments, this has been shown for both the cyclic and hysterectomized guinea-pig (Deanesly 1966). In the pig (Neill & Day 1964), if the new corpora lutea were not induced very early in the cycle, they survived the original corpora lutea for about one cycle length and prolonged the luteal phase.…”
Section: Introductionmentioning
confidence: 89%
“…Perry and Rowlands (1963) studied the effects of a number of gonadotropins in the hypophysectomized, immature guinea pig without finding a successful method to produce ovulation or corpus luteum formation. Although the successful induction of ovulation in the mature guinea pig has been reported following the administration of ovine luteinizing hormone (LH) (Dempsey et al, 1936;Deanesly, 1966;Reed and Hounslow, 1971;Donovan and Lockhart, 1974), there have been no reports of reliable ovulation induction in the cycling guinea pig in response to HCG. Quinn (1970) examined the ovarian response 18-19 h after subcutaneous injection of various doses of HCG in guinea pigs but did not quantitate follicular changes in detail and did not observe consistent ovulation induction.…”
Section: Introductionmentioning
confidence: 99%